As compreensões dos jornalistas de dados sobre transparência nos processos produtivos - Ribeiro, Bibiana Pinheiro (2022)
The present paper investigates the transparency of journalism, particularly data journalism (TRÄSEL, 2014; MASTRELA, 2019; BRENOL, 2019; GEHRKE, 2018, 2020). We understand by transparency of journalism the set of processes that has as a central objective to publicly point out to the reader the professional practices and editorial decisions that guide news production. The research path works in order to answer the question, "How do data journalists understand transparency in production processes?" Theoretically, we have transparency in journalism in studies that tense its use as a strategy for gaining trust (CHADHA, KOLISKA, 2014; KARLSSON, CLERWALL, NORD, 2014) and as a norm, a guide to journalistic work (ALLEN, 2008; KARLSSON, 2010; MEIER, REIMER, 2011; HELLMUELLER et. Al, 2013; VAN DER WURFF, SCHOËNBACH, 2014; KOLISKA, 2015; VOS, CRAFT, 2016). One of the unfoldings is the transparency seen in journalistic practice (FIRESTONE, ZIOMEK, 2005; CRAFT, HEIM, 2009; CHADHA, KOLISKA, 2014; KAMPF, DASKAL, 2014; TSETSURA, KRUCKEBERG, 2015; FENGLER, SPECK, 2019; CRAFT, HEIM, 2020). We have as specific objectives: a) To know the conceptions of data journalists about transparency in journalism; b) To categorize the understandings of data journalists about transparency in data journalism; c) To understand the implications of the notion of transparency in the productive processes of data journalism. To develop the investigation, we conducted semi-open in-depth interviews (DUARTE, 2005) and applied an electronic form. The data analysis is applied having as inspiration the Content Analysis, by Bardin (2011), with the objective of tracing categories that tell about the understandings of data journalists about transparency in the productive processes. In reading the data we found 186 textual sequences that speak about the proposed debate. In analyzing them, we recognized four categories presented in the cumulative of sequences identified, from the highest to the lowest: transparency as a practice, transparency as a value, transparency as conduct to be implemented, transparency as a contrast.